UN Sanctions and its political role in the North Korean nuclear conflict - Añaños Meza, María Cecilia (Revista Tribuna Internacional, 2021)
International sanctions, political instruments at the service of states and international organisations, enjoy currently high significance in international practice. They have been used in large cases and in different forms against sanctioned subjects like North Korea. The Democratic People’s Republic of Korea (DPRK) is target of one of the most extensive, severe and enduring sanctions ever imposed on a State since the end of World War II. They are primarily carried by a western policy of active pursue of nuclear weapons and WMD proliferation, or “counter-proliferation” policy. However, they face serious problems of justifiability which will be dealt here without losing sight of the broad political conflict linked to them. It is a critical appraisal of the occidentalist perspective with some remarks on the role of UN sanctions in the North Korean-American nuclear conflict.